1867 Mich. Pub. Acts 68 - (:unkn) unknown (My University, 1867)
Second Regular Session, No. 266, § 31, pt. 12: To regulate the buying, selling, and using of gunpowder, fire-crackers and fire-works, and other combustible materials, to regulate and prohibit the exhibition of fire-works, and the discharge of fire-crackers and fire-arms, and to restrain the making or lighting of fires in the streets and other open spaces in said village.
Keywords: DISCHARGE; TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER